2008
DOI: 10.1007/s10327-008-0116-2
|View full text |Cite
|
Sign up to set email alerts
|

Bait method to detect Pythium species that grow at high temperatures in hydroponic solutions

Abstract: Pythium helicoides, P. aphanidermatum and P. myriotylum are important pathogens that cause root rot of several crops in hydroponic culture and in ebb-and-flow irrigation systems. These species belong to a group of Pythium species that can grow at temperatures higher than 40°C. We developed a method for baiting these high-temperature Pythium species and evaluated its practicality to monitor their presence in nutrient solutions. Seeds of cucumber, tomato, radish, hemp, perilla and millet and leaves of bent grass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…The use of baits has been shown to be an effective approach for monitoring high-temperature Pythium spp. in recirculating hydorponic culture systems (Watanabe et al 2008).…”
Section: Bioassaysmentioning
confidence: 99%
“…The use of baits has been shown to be an effective approach for monitoring high-temperature Pythium spp. in recirculating hydorponic culture systems (Watanabe et al 2008).…”
Section: Bioassaysmentioning
confidence: 99%
“…; Watanabe et al . , ). However, it is difficult, laborious and time‐consuming to detect Pythium species based on morphological characteristics, partly because these characteristics vary under different culture conditions and involve intraspecific phenotypic variation (Pettitt et al .…”
Section: Introductionmentioning
confidence: 99%
“…Rapid and reliable detection is essential for an effective control of these diseases. Traditionally, detection and identification of Pythium species have been achieved by plating methods, bait methods or a combination of both (Pettitt et al 2002;Watanabe et al 2007Watanabe et al , 2008. However, it is difficult, laborious and time-consuming to detect Pythium species based on morphological characteristics, partly because these characteristics vary under different culture conditions and involve intraspecific phenotypic variation (Pettitt et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Watanabe et al (2008) concluded that seeds of hemp, perilla, and radish and leaves of bentgrass and rose were highly effective in attracting zoospores of P. helicoides, P. myriotylum and P. aphanidermatum and consequently these were employed to "catch" those species from hydroponic solutions. Other successful methods have included the use of rhododendron leaf discs and Douglas-fir needle segments in obtaining Pythium spp.…”
Section: Pythium Isolationmentioning
confidence: 99%
“…from forest soils (Weiland, 2011) and soybean leaf discs from soybean fields (Jiang et al, 2012). Thanks to the effectiveness of various methods, baiting is believed to be a useful tool for monitoring Pythium populations and forecasting disease occurrence under field conditions (Sánchez et al, 2000;Stanghellini and Kronland, 1985;Watanabe et al, 2008).…”
Section: Pythium Isolationmentioning
confidence: 99%